Multimodal participation and engagement : social interaction in the classroom. - Jacknick, Christine M. (Edinburgh University Press, 2021)
"Traditionally, teachers and researchers have looked for student participation in moments when teachers provide interactional space for it - this book takes a more holistic approach, examining how learners are participating (or not) throughout classroom interaction. It looks beyond turn-taking to consider participation as a multimodal phenomenon, including actions such as posture and gaze. It also expands the scope of classroom conversation analysis in three ways: 1) by focusing on student actions 2) by incorporating multimodal analysis, and 3) by examining both language learning contexts and non-L2 classrooms. In doing so the book uncovers how the identity of 'being a student' is enacted and provides implications for practice, teacher education and observation including emphasis on teacher interactional awareness and reflective practice."--Publisher description.
Keywords: Interaction analysis in education.; Classroom management.; Communication in education.; Interaction en éducation.; Classes (Éducation) -- Conduite.; Communication en éducation.; Classroom management; Communication in education; Interaction analysis in education